Modelando a inadimplência do IPTU no Município de Fortaleza - Bernardes, José Flávio Felix (2020)
The study proposes models to investigate the determinants of the default on the Property and Urban Territorial Property Tax (IPTU) in the municipality of Fortaleza and draws a profile of properties that account for the unpaid amount of this tax, which is their second source of their own revenue. Annual data for the referred tax in the period from 2015 to 2018 are applied to econometric models in multivariate analysis and in estimated specifications with a binary dependent variable with a sample of 530,000 property registrations obtained from the Municipal Finance Department of Fortaleza. The results allow us to infer that the default rate was lower in the areas with the highest venal value and, contrarium sensu, the default was higher in the areas with the lowest venal value. These results are supported in the literature and also reflect the disregard of the population with less purchasing power in relation to tax obligations and are reinforced by spatial analyzes of georeferencing, with indication of the areas, by Regional Executive Secretariats, which comprise the largest unpaid volume of this tax. Together, the results of the study support the development of actions for the performance of the Fiscal Audit, as well as administrative collection to optimize the municipal collection and the consequent implementation of public policies.